Relationship Between the Verbal Working Memory System and Subtypes of Reading Disability. - Basho, Surina. (2017)
Abstract: Across both research and clinical settings, memory deficits have been acknowledged as one of the major characteristics associated with developmental dyslexia. As such, a great number of studies have been conducted over the years to understand the complex relationships among dyslexia, verbal short-term memory (VSTM), and the central executive (CE). The results, however, have been mixed, potentially because few studies have differentiated subtypes of dyslexia within the samples. Further, many of the studies have focused on word-level and connected-text level reading deficits, resulting in a limited understanding of the relationship between memory and sublexical (or subword) deficits. Exploring memory in relation to subtypes may help to clarify and extend our knowledge of how specific sublexical core reading components (in particular, naming speed) interact with VSTM and CE. In the present study, the double-deficit hypothesis (DDH; Wolf & Bowers, 1999) was used to classify children with reading disabilities (RD) into subtypes (N=134, ages 7-9). The four subtypes were: phonological awareness deficits only (PD; n=33), naming speed deficits only (NSD; n=34), combined deficits (DD; n=39), and a group of children that do not fall neatly within the DDH framework but who experience fluency deficits in connected text (unclassified readers, UcRD; n=28). The main purpose of the study was to assess whether RD subtypes under the DDH have distinct patterns of VSTM and CE functioning. The results established that children with sublexical deficits (PD, NSD, and DD) all have weaknesses in their verbal working memory systems. Further, there were no significant differences in VSTM and CE profiles across the subtypes. The implications of these findings in terms of the theory, assessment, and intervention of reading disabilities are discussed.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Child Development.; Advisor: Maryanne Wolf.; Committee: Lynn Meltzer, Todd Rose, and Ranjini Reddy.; Keywords: Developmental psychology, and Educational psychology.